Highly Organized Self-Assembled Dendriplexes Based on Poly(propylene imine) Glycodendrimer and Anti-HIV Oligodeoxynucleotides - Maly, J.; Pedziwiatr-Werbicka, E.; Maly, M.; Semeradtova, A.; Appelhans, D.; Danani, A.; Zaborski, M.; Klajnert, B.; Bryszewska, M. (Current Medicinal Chemistry, 2012)
Dendrimers are artificial polymeric macromolecules which are widely considered to be a promising tool for future gene therapy applications. They have been used as efficient delivery vehicles for antisense oligonucleotides targeting the interior of cells. We demonstrate that dendriplexes formed from anti-HIV oligodeoxynucleotides ANTI-TAR, GEM91, and SREV in complex with generation 4 maltose (PPI-Mal G4) and maltotriose (PPI-Mal-III G4) modified poly(propylene imine) dendrimers are able to self-assemble into highly organized 1D and 3D nanostructures. The resulting nanostructures were characterized by fluorescence methods, laser Doppler electrophoresis, dynamic light scattering (DLS), atomic force microscopy (AFM) and molecular modeling. The results show that ANTI-TAR and GEM 91 dendriplexes self-assemble into fibrils with length scales up to several hundreds of nm. SREV, on the contrary, forms quadrilateral- like 3D nanostructures. A good correlation between the various experimental methods and molecular modeling indicates the formation of those nanostructures in solution. Space symmetry of the oligonucleotides and the resulting dendriplex monomeric units are probably the most important factors which influence the way of self-assembling.
Keywords: atomic force microscopy